2019
DOI: 10.1111/jcmm.14684
|View full text |Cite
|
Sign up to set email alerts
|

Sodium butyrate attenuates angiotensin II‐induced cardiac hypertrophy by inhibiting COX2/PGE2 pathway via a HDAC5/HDAC6‐dependent mechanism

Abstract: Sodium butyrate (NaBu) is reported to play important roles in a number of chronic diseases. The present work is aimed to investigate the effect of NaBu on angiotensin II (Ang II)‐induced cardiac hypertrophy and the underlying mechanism in in vivo and in vitro models. Sprague Dawley rats were infused with vehicle or Ang II (200 ng/kg/min) and orally administrated with or without NaBu (1 g/kg/d) for two weeks. Cardiac hypertrophy parameters and COX2/PGE2 pathway were analysed by real‐time PCR, ELISA, immunostain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
73
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(73 citation statements)
references
References 43 publications
0
73
0
Order By: Relevance
“…For quantitative reverse transcription PCR (qRT-PCR), total RNA isolation was performed as previously described 33 . Reverse transcription and SYBR green based quantitative polymerase chain reaction were performed as the manufacturer's instructions (TsingKe Biological Technology, TSE202).…”
Section: Quantitative Reverse Transcriptase Pcrmentioning
confidence: 99%
“…For quantitative reverse transcription PCR (qRT-PCR), total RNA isolation was performed as previously described 33 . Reverse transcription and SYBR green based quantitative polymerase chain reaction were performed as the manufacturer's instructions (TsingKe Biological Technology, TSE202).…”
Section: Quantitative Reverse Transcriptase Pcrmentioning
confidence: 99%
“…8, Fig. 4B) simultaneously using reported relative changes in LV mass from VO [29,42,48,[55][56][57][58][59][60] and AngII infusion [19][20][21][22][23][24][25][26] experiments in rats. To simulate VO, we set the circulatory parameters to the fitted acute VO values and maintained them throughout growth.…”
Section: Calibrating the Multiscale Model: Vo Angii E2 P4mentioning
confidence: 92%
“…Notably, the Stretch input increased acutely and gradually decreased in our VO simulations while it remained relatively constant near baseline for AngII, E2, and P4. [19][20][21][22][23][24][25][26], Progesterone (P4) infusion [28], and Estrogen (E2) infusion [53,[64][65][66]. A.)…”
Section: Uncertainty Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…17 In similar contexts, HDAC6 has been proposed as a therapeutic target for treatment of cardiovascular diseases. [15][16][17][18][19] We also recently reported that tubastatin A, an HDAC6-specific inhibitor, could increase CSE acetylation and enhance its protein levels and H 2 S production, thereby helping to attenuate the vasoconstriction and hypertension induced by AngII. 20 Moreover, HDAC6, a member of the class IIb HDAC family, exhibits distinct characters compared to other HDAC family members in that it has unique specificity for protein deacetylation of non-histone substrates such as α-tubulin, cortactin and heat-shock protein 90.…”
Section: Introductionmentioning
confidence: 92%